Analysis Of The Process Of Evaluation, Work Supervision, Policy, Supervision And Monitoring Of Puskesmas Heads Of Logistic Provision At UPTD Puskesmas Lahusa - Lurusan Hati Harefa; Wienaldi Wienaldi; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2023)
Logistics management is the science and/or art of planning and determining needs, procurement, storage, distribution, maintenance, disposal and control of medical devices. Provision of logistics at the Puskesmas is a matter that needs to be considered for its provision through a good and orderly management system. This management system can be carried out in several ways, namely through supervision, supervision, monitoring and evaluation related to the implementation of logistics provision. The purpose of this study was to analyze the evaluation process, supervision work, policies, supervision in health and health monitoring of the Head of the Puskesmas regarding the provision of logistics at the UPTD Puskesmas Lahusa. This type of research is descriptive analytic, quantitative approach with a cross sectional design. The sample in this study were all staff involved in implementing logistics provision at the Lahusa Health Center. The sampling technique is the total population, that is, the entire population is used as a research sample totaling 112 people. The results showed that all variables had a significant effect between evaluation, supervision work, policy, supervision in health and health monitoring of the Head of the Puskesmas on the provision of logistics at the UPTD Puskesmas Lahusa. The results of this study are expected to be input for the puskesmas management services to pay more attention to the implementation of logistics provision.